Fine Mapping of a Locus Underlying the Ectopic Blade-Like Outgrowths on Leaf and Screening Its Candidate Genes in Rapeseed (Brassica napus L.) - Chai, Liang; Feng, Bin; Liu, Xun; Jiang, Liangcai; Yuan, Shu; Zhang, Zhongwei; Li, Haojie; Zhang, Jinfang; Fernando, Dilantha; Xu, Chun; Cui, Cheng; Jiang, Jun; et al. (Frontiers in Plant Science, 2021)
Leaf is an important organ for higher plants, and the shape of it is one of the crucial traits of crops. In this study, we investigated a unique aberrant leaf morphology trait in a mutational rapeseed material, which displayed ectopic blade-like outgrowths on the adaxial side of leaf. The abnormal line 132000B-3 was crossed with the normal line 827-3. Based on the F2:3 family, we constructed two DNA pools (normal pool and abnormal pool) by the bulked segregant analysis (BSA) method and performed whole genome re-sequencing (WGR), obtaining the single nucleotide polymorphism (SNP) and insertion/deletion (InDel) data. The SNP-index method was used to calculate the Δ(SNP/InDel-index) and then an association region was identified on chromosome A10 with a length of 5.5 Mbp, harboring 1048 genes totally. Subsequently, the fine mapping was conducted by using penta-primer amplification refractory mutation system (PARMS), and the associated region was narrowed down to a 35.1 kbp segment, containing only seven genes. These seven genes were then analyzed according to their annotations and finally, BnA10g0422620 and BnA10g0422610, orthologs of LATE MERISTEM IDENTITY1 (LMI1) gene from Arabidopsis and REDUCED COMPLEXITY (RCO) gene from its relative Cardamine hirsuta, respectively, were identified as the candidate genes responding to this blade-like outgrowth trait in rapeseed. This study provides a novel perspective into the leaf formation in Brassica plants.